Strategi Penghidupan Rumah Tangga Pedesaan dalam Menghadapi Dampak Pandemi Covid-19 - Hendri Dony Hahury; Fransisca Soselisa (Jurnal Pengabdian Pada Masyarakat, 2021)
DYNAMICS OF RURAL HOUSEHOLDS LIVELIHOOD STRATEGY IN FACING THE IMPACT OF COVID-19 PANDEMIC. The life of rural communities is always faced with various vulnerabilities threatening their livelihoods. The vulnerability in this context refers to the Covid-19 pandemic. This pandemic has caused many community members to lose their sources of income while they are also faced with increasing and varied household needs. For this reason, they are required to be able to find new sources of income so that the needs of their household can be met. Income intensification and extensification are the ways they can take as a livelihood strategy. The purpose of this community service is to identify and describe the dynamics of livelihood strategies carried out by the rural households in dealing with the impact of Covid-19 in negeri Passo, Ambon City. The method used to achieve this goal is by combining socialization and training. The results are in the form of identification of problems, solutions and potentials of the kampung mama negeri Passo community. Furthermore, the community has various potentials to be developed but are limited by the access to assets. On the other hand, the negeri Passo community also has a social capital in the form of a “masohi” (gotong-royong) spirit to get out of the vulnerabilities that limit their livelihoods together. Their various potentials can be developed to obtain economic benefits as a household livelihood strategy by providing a concrete motivation.